A Review of the Use of Complementary and Alternative Medicines by Children with Inflammatory Bowel Disease - Day, Andrew S. (Frontiers in Pediatrics, 2013)
The Inflammatory Bowel Diseases (IBD) are diagnosed more commonly in children and adolescents. Following diagnosis, the key objectives are to achieve and then maintain remission. Although some therapies are able to effectively modify and modulate inflammatory events, none of the available interventions cure these conditions. Consequently, children and their parents face uncertainty and may look to alternative management options as ways to help their child, which may include various complementary and alternative medicines (CAM). A number of studies have shown that many children with IBD receive or are given CAM agents. This article reviews the rates and patterns of CAM use in children with IBD, and emphasises the increasing importance of these aspects of the management of children with IBD.